Lipids and their δ13C values reveal carbon assimilation and cycling in the methane-seep tubeworm Paraescarpia echinospica from the South China Sea. (August 2021) - Guan, Hongxiang; Birgel, Daniel; Feng, Dong; Peckmann, Jörn; Liu, Lei; Liu, Lihua; Tao, Jun
Abstract: Gutless tubeworms obtain their nutrition from their bacterial endosymbiotic partners, and the metazoan hosts provide the bacteria with sulfide, carbon dioxide, and molecular oxygen taken up through the plume. At seeps, tubeworms take up sulfide using their posterior end, allowing them to fix carbon dioxide and synthesize organic molecules. Compared to bulk tissue isotope compositions, lipid biomarkers and their compound-specific δ 13 C values of soft tissues allow to assign nutritional modes of endosymbionts and hosts, as well as associations between endosymbionts and the animal host. In this study, the tubeworm Paraescarpia echinospica retrieved from the Haima seeps in the South China Sea (SCS) at approximately 1400 m water depth was analyzed using 16S r RNA, bulk tissue isotopes, lipid biomarkers, and compound-specific δ 13 C values. The Lamellibrachia sp. endosymbiont, a phylotype of the Gammaproteobacteria, is a bacterium gaining energy from oxidizing sulfur compounds (thiotrophic endosymbiont). Further, six phylotypes of Gammaproteobacteria and seven phylotypes of Alphaproteobacteria were identified in the trophosome. High contents of n -C16:1ω7, n -C18:1ω7 fatty acids, and n -C16:0 and n -C18:1ω7 fatty alcohols were found in the trophosome, and somewhat lower contents in the plume and vestimentum, consistent with the prevalence of thiotrophic endosymbionts in the trophosome. The fatty acids n- C16:1ω7 and n- C18:1ω7 produced by the endosymbionts yielded δ 13 C values ranging from −34‰ to −30‰, reflecting the use of marine dissolved inorganic carbon (DIC) rather than DIC derived from anaerobic oxidation of methane. The overall small differences in δ 13 C values (Δamong tissues ≤3‰) for n -C16:1ω7 and n -C18:1ω7 fatty acids in both symbiont-containing and symbiont-free tissues appear to represent the δ 13 C signatures of the endosymbionts. Generally, n -C16:1ω7 and n -C18:1ω7 fatty acids should be more 13 C-depleted than the respective n -C16:0, n -C18:0 fatty acids resulting from desaturation. However, in this study, the saturated n -C16:0, n -C18:0 fatty acids in soft tissues were 13 C depleted by 4‰–10‰ compared to the respective n -C16:1ω7 and n -C18:1ω7 fatty acids, suggesting complex trophic interactions between P. echinospica, its endosymbionts, other bacteria living in P. echinospica, and the environment. Sterols, yielding the lowest δ 13 C values from −49‰ to −46‰, are interpreted to be derived from bioconversion of dietary sterols by the animal host. The combination of microbial diversity, bulk tissue isotopes, and lipid biomarkers used here is a valuable approach to evaluate the nutritional associations between symbionts and hosts in chemosymbiosis as well as the diet of the animal host. Highlights: The Lamellibrachia_sp. endosymbiont was the only symbiont of P. echinospica. Symbionts used CO2 as carbon source and the δ 13 C values ranged from −11‰ to −7‰. The host used more diverse carbon sources including nutrition from endosymbionts. Sterols may be derived from bioconversion of diet of the host.